2009
DOI: 10.1002/bdra.20577
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of murine limb bud ectoderm and mesoderm after exposure to cadmium or acetazolamide

Abstract: We propose that these two teratogens and others (valproic acid and ethanol) lower sonic hedgehog signaling by perturbation of zinc function in the sonic hedgehog protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 93 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…Ethanol exposure induces postaxial forelimb ectrodactyly in the mouse (Chrisman et al, 2004), a finding that characterizes Shh-null mice (Chiang et al, 2001). It has been suggested that an ethanol-induced APR results in embryonic zinc deficiency and reduces Shh signaling leading to subsequent dysmorphology (Schreiner et al, 2009).…”
Section: Cell-signaling Cascadesmentioning
confidence: 99%
“…Ethanol exposure induces postaxial forelimb ectrodactyly in the mouse (Chrisman et al, 2004), a finding that characterizes Shh-null mice (Chiang et al, 2001). It has been suggested that an ethanol-induced APR results in embryonic zinc deficiency and reduces Shh signaling leading to subsequent dysmorphology (Schreiner et al, 2009).…”
Section: Cell-signaling Cascadesmentioning
confidence: 99%
“…Shh is a Zn‐dependent developmental trigger [57], and reduced Shh expression has been implicated in ethanol‐induced postaxial forelimb ectrodactyly in the mouse [58]. Schreiner et al [59] have suggested that a state of embryonic Zn deficiency secondary to an alcohol‐induced acute‐phase response (APR) (see below [60–62]) in the mother results in reduced Shh signaling with subsequent dysmorphology [59]. This is an interesting hypothesis that merits further investigation.…”
Section: Alcohol–zn Interactionsmentioning
confidence: 99%
“…Several teratogens induce right-dominant, postaxial ectrodactyly in mouse forelimbs (i.e., an almost perfect phenocopy of the R Low /- mutant) when the animals are exposed to these agents around E9.5 (Bell et al, 2005; Schreiner et al, 2009). Interestingly, some of the teratogens, e.g., cadmium and ethanol, down-regulate endogenous Reck in ATDC5 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of teratogens, including cadmium, acetazolamide, and ethanol, are known to induce a common limb malformation in mice after treatment at E9.5 (Bell et al, 2005; Schreiner et al, 2009). This malformation (postaxial, right-dominant forelimb ectrodactyly) is almost a perfect phenocopy of R Low /- mice.…”
Section: Discussionmentioning
confidence: 99%